Pengaruh Bimbingan Klasikal Dengan Teknik Symbolic Modeling Untuk Meningkatkan Motivasi Belajar Siswa - Maramis, Resnandhi Arhab (Prosiding University Research Colloquium, 2021)
This study aims to examine the effect of classical guidance with symbolic modeling techniques to increase students' learning motivation. This research was conducted to find the data needed to find out the increase in students' learning motivation at school, so this research is a very important step. This study uses an experimental research method, namely Pre-experimental design, the research design used is a onegroup pretest-posttest design. The research sample was taken by random sampling with a total of 24 students. Collecting data using observation, interviews and questionnaires. The instrument validity test was carried out by experts and tested statistically with the help of the SPSS 25.0 application program as well as the reliability test. As for the data analysis technique using parametric statistics, namely the Wilcoxonsigned rank test with the SPSS 25.0 application program. The results showed that classical guidance with symbolic modeling techniques had an effect on increasing students' learning motivation. This is evidenced from the results of the Wilcoxon test analysis by showing the value of Sig. of 0.001 and smaller than the 0.05 significance level. So it can be concluded that classical guidance with the use of symbolic modeling techniques can increase student learning motivation.